Serious gaming as an experiential learning tool: exploring the human–water perspectives in the case of Mt. Kenya water tower - Wamucii, Charles Nduhiu; van Oel, Pieter R.; Teuling, Adriaan J.; Ligtenberg, Arend; Gathenya, John Mwangi; Speelman, Erika N. (Frontiers in Water, 2025)
Diverse stakeholders in rural landscapes commonly have distinct and often conflicting needs and interests for the available water resources resulting in complex human-water interactions, especially in water-scarce regions. In such landscapes, resolving conflicting interests among individual viewpoints and moving toward collective human–water perspectives is paramount to achieving sustainable management of decreasing water resources. Serious games have been proposed as participatory tools for (social) learning in contested landscapes, however the impact of such approaches on learning is understudied. This study addresses this knowledge gap by evaluating the ENGAGE (Exploring New Gaming Approach to Guide and Enlighten) game as a tool for fostering collective human–water perspectives. The Upper Ewaso Ng’iro basin in Kenya was selected as the study area for its complex social-ecological dynamics, characterized by the interplay of climatic variability, competing water demands, and governance challenges that shape water resource management. Through five game sessions, participants’ perspectives were assessed at three points in time: pre-game, post-game, and post-post-game, using the Q-method. Findings indicate that serious gaming enhanced awareness of catchment-scale water challenges, particularly the influence of geographic location, economic drivers, and illegal water abstractions on water availability. While immediate post-game assessments showed shifts in perspectives, long-term follow-ups revealed partial reversion to pre-game opinions, emphasizing the need for sustained engagement. This study contributes to the literature on complex human–water interactions by demonstrating the potential of serious gaming in promoting experiential learning and stakeholder engagement in water governance. The findings are relevant for socio-hydrological scientists, water resource managers, and policymakers seeking innovative approaches to conflict resolution and sustainable water management.